<h2><u>
PLEASE MARK BRAINLIEST!</u></h2>
Answer:
Let's see...
Step-by-step explanation:
- The first coin is a quarter.
- The second, third, fourth, and fifth coins are dimes.
- The sixth, seventh, and eighth coins are nickels.
That being said, what is the total value of the cents?
cents = ¢
<u>Values:</u>
Quarter = 25 ¢
Dime = 10 ¢
Nickel = 5 ¢
So,
1 quarter + 4 dimes + 3 nickels = total cents
25 + 10 + 10 + 10 + 10 + 5 + 5 + 5 = total cents
25 + 40 + 5 + 5 + 5 = total cents
25 + 40 + 15 = total cents
25 + 55 = total cents
80 = total cents
<h3><em>Our answer is 80¢</em></h3><h3><em /></h3>
I hope this helps!
- sincerelynini
Boosting this so more people can see!!
For a given function f(x) we define the domain restrictions as values of x that we can not use in our function. Also, for a function f(x) we define the inverse g(x) as a function such that:
g(f(x)) = x = f(g(x))
<u>The restriction is:</u>
x ≠ 4
<u>The inverse is:</u>
![y = 4 + \sqrt{\frac{11}{x} }](https://tex.z-dn.net/?f=y%20%3D%204%20%2B%20%5Csqrt%7B%5Cfrac%7B11%7D%7Bx%7D%20%7D)
Here our function is:
![f(x) = \frac{11}{(x - 4)^2}](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%5Cfrac%7B11%7D%7B%28x%20-%204%29%5E2%7D)
We know that we can not divide by zero, so the only restriction in this function will be the one that makes the denominator equal to zero.
(x - 4)^2 = 0
x - 4 = 0
x = 4
So the only value of x that we need to remove from the domain is x = 4.
To find the inverse we try with the general form:
![g(x) = a + \sqrt{\frac{b}{x} }](https://tex.z-dn.net/?f=g%28x%29%20%3D%20a%20%2B%20%5Csqrt%7B%5Cfrac%7Bb%7D%7Bx%7D%20%7D)
Evaluating this in our function we get:
![g(f(x)) = a + \sqrt{\frac{b}{f(x)} } = a + \sqrt{\frac{b*(x - 4)^2}{11 }}\\\\g(f(x)) = a + \sqrt{\frac{b}{11 }}*(x - 4)](https://tex.z-dn.net/?f=g%28f%28x%29%29%20%3D%20a%20%2B%20%5Csqrt%7B%5Cfrac%7Bb%7D%7Bf%28x%29%7D%20%7D%20%20%3D%20a%20%2B%20%5Csqrt%7B%5Cfrac%7Bb%2A%28x%20-%204%29%5E2%7D%7B11%20%7D%7D%5C%5C%5C%5Cg%28f%28x%29%29%20%3D%20a%20%2B%20%5Csqrt%7B%5Cfrac%7Bb%7D%7B11%20%7D%7D%2A%28x%20-%204%29)
Remember that the thing above must be equal to x, so we get:
![g(f(x)) = a + \sqrt{\frac{b}{11 }}*(x - 4) = x\\\\{\frac{b}{11 }} = 1\\{\frac{b}{11 }}*4 - a = 0](https://tex.z-dn.net/?f=g%28f%28x%29%29%20%3D%20a%20%2B%20%5Csqrt%7B%5Cfrac%7Bb%7D%7B11%20%7D%7D%2A%28x%20-%204%29%20%3D%20x%5C%5C%5C%5C%7B%5Cfrac%7Bb%7D%7B11%20%7D%7D%20%3D%201%5C%5C%7B%5Cfrac%7Bb%7D%7B11%20%7D%7D%2A4%20-%20a%20%3D%200)
From the two above equations we find:
b = 11
a = 4
Thus the inverse equation is:
![y = 4 + \sqrt{\frac{11}{x} }](https://tex.z-dn.net/?f=y%20%3D%204%20%2B%20%5Csqrt%7B%5Cfrac%7B11%7D%7Bx%7D%20%7D)
If you want to learn more, you can read:
brainly.com/question/10300045
Answer:
Tom spent $3.75 of Skittles
Step-by-step explanation:
If each Skittle packet was $1.25, then if that is multiplied by 3, the product of the equation is, 3 dollars and 75 cents/$3.75
1.25 x 3 = 3.75